Optimization principles and algorithms - Bierlaire, Michel (CRC Press, Taylor & Francis Group, 2015)
Optimization algorithms are critical tools for engineers, but difficult to use since none of them are universal in application. This introductery text builds up the knowledge set, from the basics, so that engineering students can understand the processes that govern optimization processes. Reinforcing theory with practice, the book includes discussions on how to match applications to appropiate methods and why certain approaches are not adapted to specific requirements.